"Structural Insights and Contact Network Analysis of Fusion Inhibitors Binding to SARS-CoV-2 Spike Protein" - Mohan Kumar B S; Sethupathi Raj S; Kumar; Shalini K S; V. N. Narasimha Murthy; Rudresh Kumar KJ (The Bioscan, 2023)
This study investigates the molecular interactions and dynamics of two fusion inhibitors, Happy_00 and Happy_06, targeting the cleavage sites of the SARS-CoV-2 spike protein to block viral entry. Molecular docking simulations revealed that Happy_00 performed better at the first cleavage site (Arg685/Ser686) due to its compact structure, while Happy_06, with flexible GGGS linkers, demonstrated enhanced binding at the second cleavage site (Arg815/Ser816). Molecular dynamics (MD) simulations confirmed the stability of both inhibitors, with RMSD values around 2.3–2.5 Å and steady radius of gyration (Rg). Happy_00 showed minimal residue fluctuations (RMSF < 1.5 Å), while Happy_06 exhibited higher flexibility (RMSF up to 2.3 Å), allowing it to adapt to buried binding pockets. Contact maps highlighted key interactions between the inhibitors and the spike protein, supporting the role of flexibility in enhancing inhibitor efficacy at dynamic binding sites. These findings suggest that tetanus toxoid-derived fusion peptides are promising candidates for blocking viral fusion, providing a foundation for future antiviral strategies against SARS-CoV-2